2017
DOI: 10.3991/ijoe.v13i11.7774
|View full text |Cite
|
Sign up to set email alerts
|

Using Theme-based Narrative Construct of Images as Passwords: Implementation and Assessment of Remembered Sequences

Abstract: Abstract-With many online engineering platforms such as virtual and remote laboratories designed for young or aged users, user authentication and passwords-based methods are being re-evaluated for tracking usage patterns and security. For ICT-enabled online engineering platforms, image-based humancentric approaches are gaining relevance for access frameworks. With the rubber-hose attacks, increased senior users, many existing systems are vulnerable to many attacks. This paper employs human uniqueness of narrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Ocaya [13] proposed a simplified authentication of permitted clients built-into the server, through alphanumeric username and password (issued at registration and periodically changeable). Chellaiah et al [14] suggested securing the users' authentication through narrative constructs using a sequence of cartoon images to generate an image-based password system. Krbeček & Schauer [15] also proposed to assure the security of the system employing users' registration and reservation through usernameand-password access-system, however, they focused on securing the storage of data into the Learning Management System (LMS) [16].…”
Section: Securitymentioning
confidence: 99%
“…Ocaya [13] proposed a simplified authentication of permitted clients built-into the server, through alphanumeric username and password (issued at registration and periodically changeable). Chellaiah et al [14] suggested securing the users' authentication through narrative constructs using a sequence of cartoon images to generate an image-based password system. Krbeček & Schauer [15] also proposed to assure the security of the system employing users' registration and reservation through usernameand-password access-system, however, they focused on securing the storage of data into the Learning Management System (LMS) [16].…”
Section: Securitymentioning
confidence: 99%
“…In [6], an image sequence-based authentication technique is presented. Here, a special purpose computer game is used to generate secret password.…”
Section: Literature Surveymentioning
confidence: 99%